Time-reversal-based impact-localization and haptic-feedback method for touch panels - Bai Mingsian R.; Tsai Yao Kun (My University, 2014)
The present invention provides a time-reversal-based impact-localization and haptic-feedback method for touch panels. Firstly, a plate model for an elastic plate and the impulse responses thereof are constructed according a plate theory. Next, a mathematical model is established according to the impulse responses and a time-reversal approach. When an impact force hits the elastic plate, the touched point on the elastic plate generates a touch signal, and the touch signal is received by at least a sensor at the corner of the elastic plate. The touch signal is converted into a time-reversal signal according to the mathematical model by a simulator. The time-reversal signal is reversed to the touched point for simulating reversal vibration waves of the time-reversal signal on the elastic plate, and locating the touched point.